Due diligence obligations in metal supply chains: Traders and exchanges are key sustainability actors - Christina Saulich (Stiftung Wissenschaft und Politik (SWP), 2023)
The German government intends to establish standards for responsible sourcing of metals, and laid out its objectives in a position paper in January 2023 ("Paths to sustainable and resilient raw material supplies"). German firms source much of the metals they use through traders, exchanges and over-the-counter markets. These tend to be located outside the European Union in countries whose regulations on corporate due diligence are weaker than the EU's. Given the central role of commodity traders and exchanges in securing the supply of metals and enforcing sustainability standards in metal supply chains, the German government should ensure that its implementation of its position paper devotes commensurate attention to the commodity trade. Robust supply chain legislation at the EU level, also covering the financial sector, will permit Germany to exert indirect influence on commodity traders, exchanges and over-the-counter markets.
Keywords: 320; due diligence obligations; metal supply chains; sustainability standards; European Union; green transformation; digital transformation; commodity traders; OECD; Extractive Industries Transparency Initiative (EITI)